Whatever tomorrow brings - Wick, Lori (Wick, Lori. Californians, 2007)
As the Donovans step off the clipper onto the brick-lined streets of San Francisco, the wind holds no hint that their lives are about to change forever. After a devastating tragedy, Kaitlin, the oldest daughter, must face life in rugged California. Will the men of this restless country take advantage of her innocence? Will she recognize God's unexpected gift of love? Can she keep her family safe until her father returns? -- Back cover.